Enhancing Organic Waste Management Through Simple Composting in Kemanisan Village - Sembiring, Evi Dora; Maulud, Entol Syahrafa Nasfa; Alghifari, Muhammad Imam; Azizah, Meliyana; Samsinar, Ade; Shavab, Firli Agusetiawan (EQUATOR SINAR AKADEMIA, 2025)
The mismanagement of organic waste can lead to negative impacts on both the environment and public health. In the Sarongge area, Kemanisan Subdistrict, improper disposal of organic waste without further processing is still commonly practiced. This activity aims to optimize organic waste management through socialization and training on the production of liquid and solid fertilizers using simple composters. The methods employed include participatory approaches, educational outreach, technical demonstrations, and direct community mentoring. The results of the program indicate an improvement in residents’ understanding and skills in transforming organic waste into useful products such as organic fertilizers for household farming. This initiative is expected to foster environmental awareness and encourage community self-reliance in sustainable waste management.